The antiquity of human speech as evidenced by prehistoric data - Rosiński, Franciszek M. (Anthropological Review, 1980)
The author gives a concise review of main views on morphological and cultural evidence of origin of human speech. Interpretation of observational evidence by various authors is to a certain extent contradictory. The present author is of the opinion that there would not be any serious doubts as to accepting a hypothesis that Homo sapiens neanderthalensis, and even other species of the genus Homo used, though possibly in a primitive form, vocal linguistic communication.